Wacana Filosofis Pendidikan Islam Dalam Pemikiran Tokoh Al-Ghazali - Nantasyafira, Zalfa; Shofa, Amalia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Islamic thinking about character development has existed since the beginning of Islam when the Prophet Muhammad was sent to earth to guide humanity. According to al-Ghazali, education is not just the pursuit of knowledge and skills, but rather the process of achieving spiritual and moral perfection. For al-Ghazali, education must integrate spiritual, intellectual and moral aspects to achieve human perfection. This paper is research conducted using a descriptive qualitative approach. The main source in this paper is library data in the form of texts related to the research theme. In this research, data analysis starts from data collection, data coding, data reduction and drawing conclusions. The results of the research show that according to Al-Ghazali, education aims to help humans discover their identity and God, the creator of nature. This Is a Long Term Goal. According to Al-Ghazali, the longer a student studies, the closer he gets to Allah. Meanwhile, the short term goal is to achieve a profession according to your abilities by deepening your knowledge of Fardhu Ain and Fardhu Kifayah. Al-Ghazali's thoughts about moral education are still valid today. In building a moral education system, Al-Ghazali built a moral education system aimed at one goal, namely pursuing Allah SWT. Al-Ghazali's educational thinking is religious-ethical, that is, it leads to a style of thinking that has religious value. To achieve all of this, starting with Islamic activities based on the Koran and Hadith in order to obtain happiness in this